Percolation in a random network of conducting nanotubes: a computer simulation study - Stelmashchuk, Andriy; Karbovnyk, Ivan; Bolesta, Ivan (Видавництво Львівської політехніки, 2012)
present paper reports the algorithms and the results of the conductivity percolation effect in 3D network of conducting nanotubes.
Keywords: Nanotubes; Percolation; Conductivity